Renin-Angiotensin System - Past, Present and Future 2017
DOI: 10.5772/66748
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Renin-Angiotensin System in Healthy and Pathological Pregnancies

Abstract: Introduction: Pregnancy is a physiological process that necessitates many cardiovascular and hemodynamic adaptations to ensure the survival of the foetus and well-being of the mother. The renin-angiotensin system (RAS) has been suggested as key player in many of these changes as it is critical for blood pressure control as well as fluid and salt homeostasis in the non-pregnant state. Body: Normal pregnancy is characterized by an increase in the circulating levels of prorenin, renin, angiotensinogen and angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…During physiological pregnancy, aldosterone levels increase, inducing elevated plasma volume, which is essential for the maintenance of circulating blood volume, blood pressure, and uteroplacental perfusion. Aldosterone levels remain high throughout pregnancy, suggesting a possible role in the regulation of placental and fetal development ( 198 , 199 ). Recent studies have shown the possible involvement of aldosterone in some gynecological conditions and diseases, including endometriosis combined with infertility.…”
Section: Adrenal Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…During physiological pregnancy, aldosterone levels increase, inducing elevated plasma volume, which is essential for the maintenance of circulating blood volume, blood pressure, and uteroplacental perfusion. Aldosterone levels remain high throughout pregnancy, suggesting a possible role in the regulation of placental and fetal development ( 198 , 199 ). Recent studies have shown the possible involvement of aldosterone in some gynecological conditions and diseases, including endometriosis combined with infertility.…”
Section: Adrenal Glandsmentioning
confidence: 99%
“…Recent studies have shown the possible involvement of aldosterone in some gynecological conditions and diseases, including endometriosis combined with infertility. Aldosterone may exacerbate systemic and local inflammatory states underlying endometriosis by activating mineralocorticoid receptors present in inflammatory cells ( 198 ).…”
Section: Adrenal Glandsmentioning
confidence: 99%
“…The placenta appears to be the major source for the conversion of angiotensin I into ANG-II, since the prorenin, active renin, angiotensin converting enzyme (ACE), and ANG-II have been identified in the chorion and in the placenta [88]. The physiological roles of these components have not been completely clarified, but it has been speculated that they might participate in the regulation of the blood flow [89][90][91][92].…”
Section: Changes In the Renin-angiotensin-aldosterone System During Tmentioning
confidence: 99%